Learning Outside the Classroom Increases Elementary Students' Interest and Conceptual Understanding of Mathematics: Pembelajaran di Luar Kelas Meningkatkan Minat dan Pemahaman Konseptual Matematika Siswa SD - Nuriza, Rifki; Mahmudah , Umi (Academia Open, 2025)
Background: Mathematics learning in elementary schools often faces challenges in fostering student interest and understanding due to abstract concepts and lack of contextualization. Specific Background: Traditional classroom methods may limit engagement, leading to passive learning and superficial comprehension. Knowledge Gap: There is limited research exploring the systematic integration of Outdoor Learning as a strategy to enhance mathematical understanding at the elementary level. Aim: This study aims to examine the implementation of Outdoor Learning in mathematics education and its effects on elementary students’ interest and conceptual understanding. Results: The findings reveal that Outdoor Learning significantly enhances students’ learning interest and deepens mathematical understanding by providing active, hands-on, and contextual experiences. Students engage more meaningfully when mathematical concepts are connected to real-life contexts through outdoor activities. Novelty: This study presents an in-depth case study approach in exploring how Outdoor Learning promotes meaningful learning in mathematics, filling a gap in current educational research. Implications: The study suggests that integrating Outdoor Learning in mathematics curricula can serve as an effective alternative to conventional methods, promoting higher engagement and better learning outcomes among elementary students. It underscores the need for curriculum designers and educators to adopt innovative, experiential strategies in early mathematics education. Highlights: Active Learning: Outdoor Learning promotes hands-on engagement in mathematics. Contextual Approach: Real-world contexts enhance understanding of abstract concepts. Student Motivation: Outdoor Learning increases interest and participation. Keywords: Outdoor Learning, Mathematics Education, Student Engagement, Merdeka Curriculum